Sistem Pakar Diagnosa Penyakit Anak Menggunakan Metode Forward Chaining Berbasis Web - Numan Sidik; Resti Amalia (CV. Multi Kreasi Media, 2023)
Children's health is the most important thing and is very valuable, especially for children who are in a period of growth because anyone will experience health problems, especially at a vulnerable age. However, when the child has a health problem, almost all parents bring their child to be examined by a doctor or expert, and it takes a lot of time with the limited working hours of the doctor, the large number of patients, and the high cost, so the use and utilization of computer software is necessary and would be more helpful. The purpose of this study is to implement the forward chaining method in making an expert system for diagnosing pediatric diseases, inference reasoning techniques used to reach conclusions and according to needs. The inference mechanism for diagnosing children's diseases is using a forward chaining technique (forward reasoning) which starts the search from a set of diagnostic data and facts, each data and facts that cause disease are interrelated so that they can produce diagnostic conclusions. This expert system utilizes the results of the acquisition of knowledge from experts or doctors and can be a means of assisting parents to diagnose children's diseases to find out any early symptoms experienced by children. This expert system for diagnosing children's diseases is used as a tool for parents to make decisions so that treatment can be carried out independently and without having to consult a doctor.